Bioelectric impedance analysis at different concentrations of Glucose Oxidase (GOx) - Lexequias Cabrera, Christian Hugo (2021)
The present research aims to carry out the analysis of the electrical behavior of the glucose oxidase protein (GOx) and thus be able to establish the parameters to be considered in an impedance equipment to be able to perform hemoglobin readings. From the modification of reagent strips Accu-Chek it was possible to obtain the corresponding GOx readings in 8 samples, which supported the adjustment of the optimal frequency range to be able to perform bioelectric impedance analysis in biological material. The results of the study helped to have a clearer vision to lay the foundations for a future team that aims to detect anemia due to the relationship of GOx with Hemoglobin (HbA1c).